Antimicrobial Activities of Oyster Mushroom (Plerotous ostreatus), Garlic (Allium sativum), and Ginger Extracts (Zingiber officinale) Against Some Clinical Isolates - Adenuga, Victoria Oluwapelumi; Fakoya, Soji; Sanni, Joseph Adaviruku; Adenuga, Akinola; Adenuga, Ore-ofe Oluwatoyin; Ajayi, Oluwaferanmi Timileyhin (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2024)
The prevalence of multiple drug resistance among human pathogenic bacteria necessitates a continual search for new antimicrobial medicines, particularly among plants that are frequently farmed or naturally found in our surroundings. The study aims to investigate the inhibitory effect of garlic, ginger, and mushroom extracts at different concentrations against some clinical isolates. Anti-bacterial components from mushrooms, garlic, and ginger were extracted with hot water, cold water, ethanol, and acetone, and their anti-bacterial activity was determined using the agar well diffusion method. Zones of inhibition were observed primarily on hot water extracts of mushrooms (Pleurotus ostreatus) on culture plates inoculated with Staphylococcus aureus, Escherichia coli, and Klebsiella pneumonia at 370C for 24 hours. The cold water extracts of the mushroom (Pleurotus ostreatus) gave the highest zone of inhibition of 14.0±1.0mm when used against S. aureus. For spices, the cold water extracts yielded the highest zones of inhibition of 22.0±1.0mm followed by 16.0±1.0mm as observed with ginger. The results obtained have shown clearly that the mushrooms (Pleurotus ostreatus), garlic (Allium sativum), and ginger (Zingiber officinale) extracts contain phytochemicals with some antimicrobial activities. The water extracts of the mushrooms and spices showed broad-spectrum antimicrobial activity much more than ethanol and acetone extracts. The antimicrobial activities of mushroom and garlic extracts were highly effective against the bacterial pathogens studied. However, the antimicrobial activity of the ginger extract was poor. To address the multi-drug resistance to antibiotics, I recommend: that bioactive compounds found in mushrooms, ginger, and garlic be patented and used as alternative antimicrobials.